EFEKTIVITAS PENGELOLAAN BMN DENGAN APLIKASI SIMAK-BMN DI LINGKUNGAN POLTEKKES KEMENKES YOGYAKARTA - Nuswantarina Patriani; Daris Yulianto; Arif Kuncoro Dwi Putranto; Mohammad Kus Yunanto; Fitroh Adhilla (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effectiveness of the management and accountability of State Property (BMN) which is an integral part of the management and accountability of State finances by using the SIMAK - BMN application in the Poltekkes Kemenkes Yogyakarta. The method used in this research is descriptive qualitative. Data obtained through documentation, observation, and interviews. Interviews were conducted with 11 key informants. The techniques used in analyzing the research data are data collection, data reduction, and data presentation.The results showed that the management of BMN with the SIMAK – BMN application was quite effective, which was measured through 3 indicators with each indicator consisting of 2 sub indicators and 3 supporting and inhibiting factors. The conclusions from each of these indicators and factors are as follows: 1) timely reporting and good and correct BMN administration, 2) BMN management according to the procedures and socialization of SIMAK - BMN applications have been carried out, 3) HR procurement and filling have been carried out. according to qualifications, assessment of factors 1) technically facilitates the administration of BMN, 2) operationally easy to handle, 3) economically it does not require new and paperless equipment.